2022
DOI: 10.2196/38523
|View full text |Cite
|
Sign up to set email alerts
|

Health Misinformation Across Multiple Digital Ecologies: Qualitative Study of Data From Interviews With International Students

Abstract: Background Transient migrants such as international students have received limited support from host country governments throughout the COVID-19 pandemic. An increase in misinformation, resulting in poor health outcomes for individuals, may impact an already vulnerable group. Objective Existing research examines the spread of misinformation. Similarly, there is extensive literature on the health information behavior of international students. However, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(50 reference statements)
0
2
0
Order By: Relevance
“… 37 Also, research from qualitative studies has found that people who relied on multiple channels in their media ecology for their health information were more likely to identify misinformation; this suggests that reliance on different media ecologies may insulate one from being misled. 38 These two examples are indicative that common assumptions derived from aggregated “big” data from social media may well be missing the mark if the context of individuals was not given due attention.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Also, research from qualitative studies has found that people who relied on multiple channels in their media ecology for their health information were more likely to identify misinformation; this suggests that reliance on different media ecologies may insulate one from being misled. 38 These two examples are indicative that common assumptions derived from aggregated “big” data from social media may well be missing the mark if the context of individuals was not given due attention.…”
Section: Discussionmentioning
confidence: 99%
“…The study deliberately targeted a group of people who use the internet continually and who present a wide range of demographic features to be tested. By definition, however, the study excluded all other social groups and even within this group was limited to domestic students, who might be less vulnerable to false rumours originating in their home country than international students reading the same rumours (Bahl et al, 2021;Bahl et al, 2022). The study also did not test the possibility that Chinese students might resemble their foreign student counterparts in being less sceptical about online information than the general public (Metzger et al, 2003) or that they may be less vulnerable to rumours than aged persons in China (He et al, 2019).…”
Section: Jices 222mentioning
confidence: 99%